Resilience and associated factors in women survivors of Intimate Partner Violence: a systematic review - Fernández Álvarez, Natalia; Fontanil Gómez, Yolanda; Alcedo Rodríguez, Ángeles (Anales de Psicología / Annals of Psychology, 2022)
Most research on Intimate Partner Violence against women (IPV) has tended to present women as passive victims, but in recent years, there has been an increase in studies adopting a strengths-based approach. The aim of the present study is to review the empirical literature about resilience in women survivors of IPV to (a) analyze the consensus on the definition and assessment of resilience; (b) study the correlates of resilience; and (c) reflect on the applicability of such knowledge in policies and professional practice. Following PRISMA guidelines, a systematic search was carried out in the Scopus, WoS and PsycINFO databases. The search yielded 42 articles published in English or Spanish over an unlimited timeframe. Results showed that process-oriented, trait-oriented, and outcomes-oriented definitions of resilience were all adopted in the research and that assessment methods also differed across studies. Individual, relational, and contextual factors were found as resilience correlates. There is a need for a theoretical consensus and for research on the mechanisms through which vulnerability or protective factors exert their influence on groups with specific risk conditions. Finally, governments and institutions should take actions to support women and children and to prevent future IPV.